Development of Digital Low-level RF System of S-band Linac - XIE Chunjie;ZHU Wenchao;FENG Guangyao;WANG Lin;ZHOU Zeran (Yuanzineng kexue jishu, 2023)
The S-band linac is widely used in accelerator laboratories at home and abroad, including Hefei Light Source. The low-level RF system is used to monitor and control the solid state amplifier, klystron and cavities, etc., which has an important influence on the beam current stability as a part of the microwave system of linac. To meet the high acquirement of the quality of beam, the S-band digital low-level RF system was developed. The self-developed digital low-level RF system was introduced in this paper from three aspects: system architecture and hardware design, control algorithms and software design and performance test. The self-developed low-level RF system includes signal source, frequency synthesis system and IF signal processor. The signal source produces a signal with a frequency of 2 856 MHz and a phase noise of 18.05 fs. And the frequency synthesizer system generates LO signal (2 829.56 MHz) for frequency conversion and CLK signal (105.76 MHz) for digital signal processor. They realize multi-channel low phase noise signal outputs. The self-developed low-level IF signal processor adopts domestic chip, and adds ST optical port and SFP to improve the anti-interference and data transmission ability of the system. It consists of three modules, including RF module, digital module and control module. The RF module converts the RF signal from 2 856 MHz to 26.44 MHz and sends it to the digital module. The digital module finishes analog/digital conversion and the calculation of the digital signal. The control module is the communication interface between digital signal processor and center control system. The system uses IQ orthogonal demodulation and Cordic algorithm to achieve the amplitude and phase of the microwave system used for PI closed-loop control. The related control software was developed based on EPICS, and the manmachine interface was designed. The operator interface was developed based on phoebus and it realizes waveform display (raw data, IQ and amplitude and phase), parameter setting (attenuation value, feedback parameters and feedforward table parameters) and operation status monitoring. The off-line experiments show that the short-term amplitude stability of the self-developed low-level RF system is better than 0.01%, and the short-term phase stability is better than 0.01°. The on-line beam experiments show that the closed-loop phase stability in the cavity is about 0.1°. The self-developed low-level system partially replaces the imported low-level system of linear injector of Hefei Light Source user device and it realizes long-term stable operation.